Clinical Efficacy of Pulsed Radiofrequency Combined with Intravenous Lidocaine Infusion in the Treatment of Subacute Herpes Zoster Neuralgia - Wanyun Zhang; Chunjing He (Pain Research and Management)
Objective. Under the guidance of a digital subtraction angiography (DSA) machine, via fluoroscopic imaging techniques, patients diagnosed with herpes zoster neuralgia at the subacute stage, where self-reported pain lasts between 30 and 90 days, were treated with nerve pulsed radiofrequency surgery combined with intravenous lidocaine infusion or saline infusion as control. This study explores the clinical efficacy, safety, and clinical value of the combined treatment compared with nerve pulsed radiofrequency surgery alone. Methods. In this study, 72 patients diagnosed with herpes zoster neuralgia at the subacute stage were randomly divided into two groups with matched gender, age, and clinical symptoms. Both groups received pulsed radiofrequency surgery for the affected nerve segments under DSA fluoroscopy. Five days after the operation, 0.9% saline was administered daily for five consecutive days (50 ml per day, intravenous infusion) to group A (n = 36), and lidocaine was administered daily for five consecutive days (3 mg per kg per day, intravenous infusion) to group B (n = 36). Patients with poor pain control during the treatment were given 10 mg morphine tablets for pain relief to reach visual analog scale (VAS) ≤4 points. Data of the following categories were collected: VAS score, self-rating anxiety scale (SAS) score, depression self-rating scale (SDS) score, Pittsburgh sleep quality score (PSQI), 45 body area rating scale score, skin temperature measurement using infrared thermography, analgesic drug use before and after treatment at six different time points: before surgery (T0), one day after surgery (T1), three days after surgery (T2), five days after surgery (T3), one month after surgery (T4), and two months after surgery (T5). Blood was collected from all patients in the morning before surgery and right after the last intravenous infusion of lidocaine at T3. Serum inflammatory indexes including white blood cell count, lymphocyte count, neutrophils count, erythrocyte sedimentation rate count, C-reactive protein (CRP) level, calcitonin gene-related peptide (CGRP) level, and interleukin-6(IL-6) level were determined. Lastly, the incidence of complications and adverse reactions throughout the study was recorded. Results. In total, 64 out of 72 patients completed the whole study. Two patients met the exclusion criteria in group A, one patient refused to participate, and one was lost to follow-up. Two patients met the exclusion criteria in group B, and two were lost to follow-up. Three patients in group B experienced vomiting during lidocaine treatment. The adverse symptom was relieved after symptomatic treatment. No patients in the two groups had severe complications such as hematoma at the puncture site, pneumothorax, and nerve injury. Compared with before treatment, the mean of VAS score, SAS score, SDS score, PSQI score, and skin temperature of both groups at each time point after interventional surgery were all significantly reduced. Furthermore, at each time point after surgery, the above indicators of group B patients were significantly lower than those of group A patients. After treatment, the consumption of analgesics in both groups was significantly lower than before treatment. Compared with group A, the consumption of analgesics was also significantly lower in group B. In addition, serum inflammatory indexes at the T3 time point of the two groups of patients were lower than T0. Among them, the erythrocyte sedimentation rate, CRP level, CGRP level, and interleukin-6 level of group B were significantly lower than those of group A. The incidence of postherpetic neuralgia (PHN) in group B patients (6.25%) was also lower than that in group A patients (25%). Conclusion. DSA-guided nerve pulse radiofrequency surgery combined with intravenous lidocaine infusion can effectively relieve pain in patients diagnosed with herpes zoster nerves at the subacute stage, reduce the number of analgesic drugs used in patients, reduce postherpetic neuralgia incidence rate, and improve sleep and quality of life.